A percepção dos produtores rurais familiares acerca da agregação de valor nas hortifrutícolas, na modernidade líquida - Silva, Ana Paula de Lima da (2021)
This thesis aimed to analyze the perception of family farmers about the ways of adding value to their horticultural products, in liquid modernity. This objective was defined with the intention of filling a research gap, since there are no studies that analyze the perception of family farmers about the addition of value to their horticultural products, in the context of the theory of liquidity. To meet the proposed objectives, an exploratory and descriptive research with a phenomenological approach was used. The data analysis was performed by means of a qualitative nature, with the support of NVivo® and UCINET® software, in a socially relevant sample of ten rural family farmers with the ability to describe their lived experiences. The sample was approached using the Snowball method and a cross-sectional research study. It is concluded that the family farmers do not have enough clarity on what value addition is, despite making use of some variables such as agribusiness, production system and organic certification, short marketing circuits and agroecological production system. It was found that the producers received little or no technical assistance, and sometimes, when they get it, it is from an agricultural technician or agronomist who is a salesperson, which can lead to a biased diagnosis and prescription. In addition, it was found that family farmers do not seek information about the market in which they operate, nor about the behavior of their consumers. This combination of lack of knowledge about the market and consumers causes blindness, since it is impossible to add value, because they lack clarity about the concept of what it is, and even if they knew what it means, they don't know what value is for their customer, since they don't know it. All this shows that family farmers are not prepared to face the challenges contained in today's liquid modernity, which has an increasingly fluid and malleable context, and has as its main characteristic the speed of change in everything, including commercial relations. This scenario demands from family farmers, as well as any other producer/supplier, flexibility and adaptation in the forms of commercialization and management of the property, so that it is possible to serve their consumers, improve their earnings and, consequently, their quality of life, and still be motivated to remain and live from the property.